Math problem-solving and cognition among emerging bilingual children at risk and not at risk for math difficulties. Issue 4 (18th May 2020) - Swanson, H. Lee; Kong, Jennifer; Petcu, Stefania D.
ABSTRACT: Cognitive processes that underlie individual differences in mathematical problem-solution accuracy in elementary emerging bilingual children (English Learners) at risk and not at risk for math problem-solving difficulties (MD) were examined. A battery of tests was administered in both English and Spanish that assessed problem-solving, achievement, and cognitive processing in children in first ( N = 155/MD N = 23), second ( N = 129/MD N = 44) and third grades ( N = 110/MD N = 39). The results were that (a) the executive component of working memory (WM) predicted MD status independent of measures of fluid intelligence, reading, calculation, knowledge of algorithms, processing speed, short-term memory, and inhibition, (b) low performance on Spanish measures of numeracy and executive component of WM were major predictors of the odds of being classified as MD and (c) bilingual proficiency primarily moderated English rather than Spanish measures of cognition. The results support the notion that the executive system of WM is an important predictor of emerging bilingual children's math problem-solving difficulties.